The Influence of Employee Education and Work Experience on Employee Performance and Employee Loyalty - Jumawan, Jumawan; Ali, Hapzi; Nyoman Sawitri, Ni; Tusholeha Rony, Zahara (Siber International Journal of Digital Business (SIJDB), 2024)
Purpose – The purpose of this writing is to build a hypothesis regarding the influence between variables which can later be used for further research within the scope of human resource management. Design/methodology/approach – The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. Findings – The results of this research are that: 1) Employee education influences employee performance; 2) Work experience influences employee performance; 3) Employee education influences employee loyalty; 4) Work experience influences employee loyalty; and 5) Employee performance influences employee loyalty. Research limitations/implications – The limitations of the data used in this research make the results less than optimal. Practical implications – This research is useful for company management in seeing whether employee education levels influence employee performance and employee loyalty.